2022
DOI: 10.3390/diagnostics12102345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acute Lesions of the Biceps Pulley in Patients with Traumatic Shoulder Dislocation Using MR Imaging

Abstract: Background: Shoulder dislocations represent common injuries and are often combined with rotator cuff tears and potentially damage to the biceps pulley. Purpose: To assess the occurrence and type of biceps pulley lesions in patients after traumatic anterior shoulder dislocation using 3T MRI. Methods: Thirty-three consecutive patients were enrolled between June 2021 and March 2022 (14 women, mean age 48.0 ± 19 years). All patients underwent MR imaging at 3 T within one week. Images were analyzed for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The resolution of standard 1.5T MRI is inadequate for distinguishing between these different components. 15 According to our arthroscopic reports, there was concordance with previous studies regarding SGHL lesions in various patient groups. 7,16 Martetschläger et al 2 found that 36% of their patients with BP lesions had intact medial CHL/SGHL complexes with lateral CHL lesions, making them unclassifiable by Habermeyer's classification.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The resolution of standard 1.5T MRI is inadequate for distinguishing between these different components. 15 According to our arthroscopic reports, there was concordance with previous studies regarding SGHL lesions in various patient groups. 7,16 Martetschläger et al 2 found that 36% of their patients with BP lesions had intact medial CHL/SGHL complexes with lateral CHL lesions, making them unclassifiable by Habermeyer's classification.…”
Section: Discussionsupporting
confidence: 90%
“…Martetschläger et al classification 2 relied on arthroscopic findings and classified BP lesions into medial sling (medial CHL/SGHL), lateral sling (lateral CHL) injuries or combined. The resolution of standard 1.5T MRI is inadequate for distinguishing between these different components 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found a positive correlation between pulley structure injury and Lesions of LHBT.The pulley structure of LHBT comprises the superior glenohumeral ligament (SGHL), the coracohumeral ligament (CHL), the supraspinatus muscle, and the subscapularis tendon, which is a soft tissue stabilizing device before the biceps long head tendon enters the bone pulley groove. Pulley structure injury is an important reason for the anterior pain of the shoulder joint [16][17][18]. Recently, more attention has been paid to pulley injury.…”
Section: Discussionmentioning
confidence: 99%